2009
DOI: 10.1105/tpc.108.061887
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Cell Death in Rice Is Confined to Cells with a Distinct Molecular Identity and Is Mediated by Ethylene and H2O2 through an Autoamplified Signal Pathway

Abstract: Rice (Oryza sativa) forms adventitious root primordia at stem nodes during normal development. Root emergence is preceded by ethylene-induced, H2O2-mediated local death of epidermal cells. Exogenous H2O2 or enhancement of endogenous H2O2 promoted epidermal cell death in a dose-dependent manner. Inhibition of NADPH oxidase lowered ethylene-induced cell death rates. Inhibition of ethylene perception by 1-methylcyclopropene did not abolish H2O2-induced cell death, indicating that H2O2 acts downstream of ethylene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(166 citation statements)
references
References 82 publications
4
158
1
3
Order By: Relevance
“…This cell-to-cell mechanosignaling enabled emergence of the adventitious root. Remarkably, comparison of the transcriptomes of epidermal cells located directly above the primordium with those nearby indicated that there was spatial priming of programmed cell death prior to its elicitation (Steffens and Sauter, 2009). The mRNAs enriched above the subtending primordium were associated with ethylene biosynthesis, whereas the depleted transcripts included one encoding a metallothionein that negatively regulates cell death.…”
Section: Morphological and Anatomical Adaptations That Increase Floodmentioning
confidence: 99%
“…This cell-to-cell mechanosignaling enabled emergence of the adventitious root. Remarkably, comparison of the transcriptomes of epidermal cells located directly above the primordium with those nearby indicated that there was spatial priming of programmed cell death prior to its elicitation (Steffens and Sauter, 2009). The mRNAs enriched above the subtending primordium were associated with ethylene biosynthesis, whereas the depleted transcripts included one encoding a metallothionein that negatively regulates cell death.…”
Section: Morphological and Anatomical Adaptations That Increase Floodmentioning
confidence: 99%
“…Additional factors, such as hypoxia, might feed into the model presented here but are not essential for reactivation of the primordia. An important distinction between the S. dulcamara and rice models for AR reactivation is the target tissue: while in rice the epidermal cells are the main target of the ethylene-dependent activation pathway (Steffens and Sauter, 2009), AR dormancy does not seem to depend on mechanical restriction by the epidermis in S. dulcamara. (Supplemental Fig.…”
Section: A Model For Hormonal Regulation Of Ar Activationmentioning
confidence: 99%
“…The well-described mechanism for flooding-induced breaking of AR primordia dormancy in rice involves hydrogen peroxide-dependent epidermal cell death, resulting in removal of the physical restriction to primordium growth (Steffens and Sauter, 2009). In S. dulcamara, the mechanism is fundamentally different, as AR primordia are located much deeper, covered by several layers of cortex cells (Fig.…”
Section: Submergence Causes Extensive Transcriptomic Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher plants are aerobic organisms that suffer serious physical damage and rapidly die when oxygen availability is limited because of soil flooding. [1][2][3][4] Low oxygen shifts energy metabolism from aerobic to anaerobic, which in turn adversely affects nutrient and water uptake. Under oxygendeficient conditions, production of both hydrogen peroxide (H 2 O 2 ) and ethylene is triggered by hypoxia signaling.…”
Section: R Eactive Oxygen Species (Ros)mentioning
confidence: 99%